Evaluation of the Clinical Characteristics of Patients with Food Protein-Induced Enterocolitis Syndrome: A Multicenter Study - Metbulut, Azize Pinar; Ozen, Selime; Kendirci, Nergiz; Guc, Belgin Usta; Guvenir, Hakan; Vezir, Emine; Orhan, Fazil (Karger, 2022)
Introduction: Food protein-induced enterocolitis syndrome (FPIES) is a rare non-IgE, cell-mediated food allergy disorder. We aimed to report the demographic characteristics, clinical features, and management of pediatric patients with FPIES. Methods: This retrospective study included all children diagnosed with FPIES at the pediatric allergy departments of the participating twelve study centers from January 2015 to November 2020. Results: A total of 73 patients (39 males, 53.4%) with a male/female ratio of 1.1 were included in the study. The median (interquartile ranges) age at symptom onset was 6 months (0.5-168, 4-9.5). The most frequent offending foods were cow's milk, egg's yolk, fish, and egg's white, identified in 38.4% (n = 28), 32.9% (n = 24), 21.9% (n = 16) and 20.5% (n = 15) of the patients, respectively. The total number of reported FPIES episodes was 290 (3.9 episodes per child). Oral food challenge (OFC) was performed in 54.8% (n = 40) of the patients, and tolerance was detected in 17 OFCs (42.5%) at a median age of 15 months (range 8-132 months). Conclusion: FPIES is a non-IgE-mediated food hypersensitivity that commonly affects infants and is often misdiagnosed. The pathophysiology of the disease remains unclear and the low awareness of FPIES among physicians and parents highlights the need for more education.
Keywords: Food protein-induced enterocolitis syndrome; Food allergy; Oral food challenge; Children